Like Father Like Son: Cultural and Genetic Contributions to Song Inheritance in an Estrildid Finch - Lewis, Rebecca N.; Soma, Masayo; de Kort, Selvino R.; Gilman, R. Tucker (Frontiers in Psychology, 2021)
Social learning of vocalizations is integral to song inheritance in oscine passerines. However, other factors, such as genetic inheritance and the developmental environment, can also influence song phenotype. The relative contributions of these factors can have a strong influence on song evolution and may affect important evolutionary processes, such as speciation. However, relative contributions are well described only for a few species and are likely to vary with taxonomy. Using archived song data, we examined patterns of song inheritance in a domestic population of Java sparrows (Lonchura oryzivora), some of which had been cross-fostered. 676 songs from 73 birds were segmented and classified into notes and note subtypes (N = 22,972), for which a range of acoustic features were measured. Overall, we found strong evidence for cultural inheritance of song structure and of the acoustic characteristics of notes; sons’ song syntax and note composition was similar to that of their social fathers and was not influenced by genetic relatedness. For vocal consistency of note subtypes, a measure of vocal performance, there was no apparent evidence of social or genetic inheritance, but both age and developmental environment influenced consistency. These findings suggest that high learning fidelity of song material, i.e., song structure and note characteristics, could allow novel variants to be preserved and accumulate over generations, with implications for evolution and conservation. However, differences in vocal performance do not show strong links to cultural inheritance, instead potentially serving as condition dependent signals.